Ibrutinib versus rituximab in relapsed or refractory chronic lymphocytic leukemia or small lymphocytic lymphoma: a randomized, open‐label phase 3 study. (13th March 2018) - Huang, Xiaojun; Qiu, Lugui; Jin, Jie; Zhou, Daobin; Chen, Xiequn; Hou, Ming; Hu, Jianda; Hu, Yu; Ke, Xiaoyan; Li, Junmin; Liang, Yingmin; Liu, Ting; et al.
Abstract: In the Asia‐Pacific region, treatment options are limited for patients with relapsed/refractory chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). Rituximab is widely used in this setting when purine analog‐based therapies are not appropriate. We evaluated the efficacy and safety of ibrutinib compared with rituximab in a randomized, open‐label phase 3 study in predominantly Asian patients with relapsed/refractory CLL/SLL. Patients ( N  = 160) were randomly assigned 2:1 to receive 420 mg ibrutinib ( n  = 106) until disease progression (PD) or unacceptable toxicity or up to six cycles of rituximab ( n  = 54). The primary endpoint was investigator‐assessed progression‐free survival (PFS); key secondary endpoints were overall response rate (ORR), overall survival (OS), and safety. Rituximab‐treated patients could crossover to receive ibrutinib after confirmed PD. At data cutoff, median treatment duration was 16.4 months for ibrutinib and 4.6 months for rituximab. Ibrutinib significantly improved PFS (hazard ratio [HR] = 0.180, 95% confidence interval [CI]: 0.105–0.308). ORR was significantly higher ( P  <   0.0001) with ibrutinib (53.8%) than with rituximab (7.4%). At a median follow‐up of 17.8 months, ibrutinib improved OS compared with rituximab (HR = 0.446; 95% CI: 0.221–0.900; P  =   0.0206). Overall incidence of adverse events (AEs) was similar between treatments and was not exposure‐adjusted. With ibrutinib, most common AEs were diarrhea and platelet count decreased; with rituximab, most common AEs were neutrophil count decreased and platelet count decreased. Grade ≥3 AEs were reported in 82.7% of ibrutinib‐treated patients and 59.6% of rituximab‐treated patients. Ibrutinib improved PFS, ORR, and OS compared with rituximab and displayed a manageable safety profile in Asian patients with relapsed/refractory CLL/SLL. Abstract : To our knowledge, this report is the first study of ibrutinib in a predominantly Asian population of patients with relapsed/refractory CLL/SLL and the first to compare ibrutinib with rituximab. Our results show that ibrutinib significantly improved progression‐free survival, overall response rate, and overall survival compared with rituximab. Ibrutinib displayed a manageable safety profile with no new or unexpected events reported. These findings are consistent with previous studies of single‐agent ibrutinib and demonstrate the efficacy and safety of ibrutinib in a predominantly Asian population of patients.